New microRNA-based therapies reveal common targets in paediatric medulloblastoma and adult glioblastoma - Denis Mustafov; Laura Thomas; Shoib S. Siddiqui; George I. Lambrou; Maria Braoudaki (Scientific Reports)
Abstract Medulloblastoma (MB), the most prevalent brain malignancy in children, presents significant challenges in paediatric oncology due to its aggressiveness and potential for relapse. Tailored treatments are crucial to mitigate treatment-related toxicities and long-term side effects on developing brains. Our study aimed to identify therapeutic targets for paediatric MB and explore common miRNA biosignatures with glioblastoma (GB), the most aggressive adult brain tumour. High-throughput small-RNA sequencing identified miR-206 and miR-383 as highly downregulated in MB samples, suggesting their tumour suppressor properties. Bioinformatics analysis identified CORO1C and SV2B as their targets. RT-qPCR, western blotting, and immunohistochemistry confirmed their overexpression in MB and GB. Elevated CORO1C expression was also found in adult MB and GB tissue samples. The role of both miRNAs on their target genes was validated through in vitro functional assays. Our study uncovers the potential role of miR-206/CORO1C and miR-383/SV2B axes as innovative therapeutic targets for combating aggressive paediatric and adult brain malignancies.